ANALYSIS OF THE INFLUENCE OF WORKPLACE ENVIRONMENTAL HEALTH CONDITIONS ON THE QUALITY OF HEALTH SERVICES AND PATIENT SATISFACTION AT EVI MARELAN PRIMARY CLINIC - Akhyar Al Fauzi Lubis; Ermi Girsang; Sri Lestari Ramadhani Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Clinics are healthcare facilities that provide medical services to the community. This study aims to analyze the influence of workplace environmental health conditions, healthcare service quality, and human resource (HR) competence on patient satisfaction at Evi Primary Clinic. Despite being accredited and having a strong vision, the clinic still receives complaints regarding suboptimal services and facilities.Using a quantitative analytic correlational design with a cross-sectional approach, this study examined variable relationships at a single point in time. The population included all patients visiting the clinic within one month, with data collected through questionnaires and interviews. A total sampling technique was applied, and the data were analyzed using univariate, bivariate (Chi-Square), and multivariate (Discriminant Analysis) methods.Results show that HR competence significantly influences healthcare service quality, with a coefficient of 0.806 (p = 0.000), and also impacts patient satisfaction (coefficient 0.609; p = 0.000). Most respondents (62.8%) rated HR competence as fair, and 19.9% as good. Workplace environmental conditions and health facilities also significantly influence service quality (coefficient 0.639; p = 0.000) and patient satisfaction (coefficient 0.527; p = 0.000). Multivariate analysis further revealed that facilities affect service quality with a coefficient of 0.748.In conclusion, HR competence, healthcare facilities, and service quality all significantly affect patient satisfaction. A comprehensive approach is needed to enhance staff competence, improve infrastructure, and optimize service procedures. These strategies are essential for achieving high patient satisfaction and realizing the clinic’s mission of delivering excellent healthcare.